A Malay Cinderella: Chendera Lela and Modernity in Colonial Malaya - Ahmad, Siti Nuraishah (2021)
Charles Perrault’s version of the Cinderella story, Cendrillon ou la Petite Pentoufle de Verre (Cendrillon, or The Little Glass Slipper; 1698) is perhaps the most well-known rendition of the centuries-old tale around the world. Its adaptation into animated or live-action films by the Hollywood film industry in the mid-to-late twentieth century has made the story familiar to millions of viewers, young and old. Interestingly, Perrault’s version also made its way into Malay literature through an adaptation and translation, Chӗndӗra Lela (1931) under the auspices of the Sultan Idris Training College’s Malay Translation Bureau. Part of the Malay Home Library Series published by the Bureau, Chӗndӗra Lela recasts Perrault’s rendition into a version deemed fit for a modern Malay readership in British-ruled Malaya. This paper attempts to trace the literary journey of Perrault’s Cinderella/Cendrillon into Malay, looking at the role of English translations of Perrault’s story, literary and cultural motifs from classical Malay literature and the book’s Orientalist illustrations, resulting in an eclectic, hybrid text.